Efektifitas Penggunaan Google Formulir Dalam Ujian Online Bahasa Jepang di SMAN 9 Pekanbaru - Yohanna Tasya; Yenny Aristia Nasution; Merri Silvia Basri (Jurnal Pendidikan Bahasa Jepang Undiksha, 2022)
Google Forms is a system in the form of form templates that can be used for the purpose of obtaining user information. The purpose of this study was to describe the effectiveness level of using Google Forms in Japanese online exams during the COVID-19 pandemic. The researcher will measure the effectiveness of the online Japanese language exam using quantitative research methods with the results in the form of percentages. The data and data sources used are the results of questionnaires from students and teachers of SMAN 9 Pekanbaru and the results of interviews with Japanese language teachers at SMAN 9 Pekanbaru. The theory used to measure the effectiveness of Google Forms is DeLone and McLean who review information systems from system quality, information quality, and user satisfaction. The results of the research on the effectiveness of Google Forms in the Japanese online exam at SMAN 9 Pekanbaru in terms of system quality are 80% in the effective category, 81% information quality in the effective category, and 79% user satisfaction in the effective category. The average value of all aspects is 80% with the effective category. Google Forms are effective for Japanese online exams at SMAN 9 Pekanbaru during the Covid-19 pandemic.